Theoretical study of the desorption of neutral and ionic alkali metal atoms from the excited Li+(H2O)n = 1‐4 and Na+(H2O)n = 1‐4 cluster models: Electronic excitation charge transfer. Issue 4 (19th November 2019) - Farrokhpour, Hossein; Khoshkhou, Samaneh
Abstract: In this work, the potential energy curves of several low‐lying excited states of M + (H2 O)n = 1‐4 (M = Li and Na) clusters with one M─O bond, related to the stretching of their M─O bond, were calculated in the gas phase. The time‐dependent density functional theory and direct‐symmetry‐adapted cluster‐configuration interaction were used in this study separately. Theoretical calculations showed that the charge transfer occurred between M + and (H2 O)n in the excited clusters so that the neutral metal atom was obtained at the dissociation limit of the potential curves. The excited potential curves of clusters were also calculated in the presence of the electrostatic field of water (EFW), and it was found that the charge transfer was blocked in the presence of EFW. The effect of the size of the (H2 O)n cluster on the shape of the excited potential curves was investigated to observe how the M─O bond was affected in the excited states depending on the (H2 O)n size. It was found that the increase in the size of the (H2 O)n cluster increased the number of bonding excited potential curves. The difference between the electron density of the excited and ground electronic states was calculated to see how the charge transfer was affected by the size of the (H2 O)n cluster. Abstract : In this work, hydrated alkali cation models with one M─O bond are investigated in their excited bonding and dissociative states. The effect of the size of the water cluster and the arrangement of water molecules in it on the excited potential curves are studied. The charge transfer between the metal ion and water cluster was observed in the gas phase due to the excitation. The electrostatic field of the solvent blocks this charge transfer.